ETIKA PSIKOANALISIS SIGMUND FREUD SEBAGAI LANDASAN KESALEHAN SOSIAL - ISHAK HARIYANTO (Al-Tazkiah : Jurnal Bimbingan dan Konseling Islam, 2016)
Ethics is the important role in human life, just imagine aworld without ethics and morals, then the consequences will be a world where no one has a conscience and no one willever feel guilty or sorry for what they did or did not do. According to Freud, he said that human is deterministic because isdetermined by unconsciousirrational power, the unconscious motivation, biological encouragement, and instinctive encouragement. Human has always beenthe pursuit of perfection to get happiness and to avoid unhappiness.The purpose of this research was to describe about the psychoanalysis ethics of Sigmund Freud and to apply it in social life in order to create the social piety. During Freud psychoanalysisas ifts just in medicine, counseling and religion. But what about the psychoanalysis ethics of Sigmund Freud are manifesting in the structure of human personality likeId (Das Es), Ego (Das Ich), Super ego (Das Ueber Ich) were compared in the context of social piety, so it would create the dialogue between individual piety and social piety, to establish the whole system of unity and run circularly.